Uric acid lowering therapy: prescribing patterns in a large cohort of older adults. Issue 5 (29th August 2007) - Solomon, D H; Avorn, J; Levin, R; Brookhart, M A
Abstract : Background: Uric acid lowering therapy (UALT) is considered a chronic treatment for gout. Relatively little is known about adherence to UALT. Methods: We assessed adherence with UALT over a 1-year study period among 9823 older adults enrolled in a pharmacy benefit program. Two adherence measures were calculated, the percentage of days covered (PDC) and the time until an extended break (at least 60 days) in treatment. A PDC <80% was considered poor adherence and its predictors were examined in multivariable logistic models. Results: The mean (SD) PDC was 54% (36%) with 64% of patients considered poorly compliant over the study period. A total of 56% had experienced an extended break in UALT. Predictors of poor adherence included younger age (odds ratio (OR) 1.50, 95% CI 1.33–1.69 for ages 65–74 compared with 85 and above) and African–American race (OR 1.86, 95% CI 1.52–2.27 compared with Caucasian race). Most patients (93%) received their initial UALT prescription from a non-specialist and this also predicted poor adherence (OR 1.15, 95% CI 0.96–1.38 compared with rheumatologists or nephrologists). Conclusion: Adherence with UALT is poor. While uric acid levels were not measured in this study, poor adherence with UALT is likely to reduce attainment of goal uric acid levels.